Determinants of Plasma Ferritin at 3 Months of Age Among Rural Bangladeshi Infants From the JiVitA-3 Trial. (7th June 2021) - Zhang, Junmeng; Schulze, Kerry Jean; Wu, Lee S-F; Baker, Sarah; Shaikh, Saijuddin; Ali, Hasmot; Labrique, Alain; West, Keith Jr; Christian, Parul
Abstract: Objectives: Ferritin, a biomarker of iron stores, is rarely reported in infants despite a known role for iron in growth and development. Iron stores accumulated in utero decline in infancy, although breastmilk iron supports infant status. In rural northwest Bangladesh, an iron-replete area, infants are small and prone to common illnesses despite prevalent breastfeeding. We explored determinants of ferritin in 3 mo old infants in this setting. Methods: In a double-blind, cluster-randomized trial (JiVitA-3) of multiple micronutrient or iron-folic acid supplementation from pregnancy ascertainment to 3 mo postpartum, maternal and infant hemoglobin (Hb), anthropometry, and plasma were obtained 3 mo after birth. Growth was assessed as weight gain since birth. In a preliminary analysis (n = 378), infant plasma ferritin, maternal ferritin, and infant α1-acid glycoprotein (AGP), a biomarker of inflammation, were assessed. Distributions are shown as mean ± SD or median (IQR) if skewed; associations of infant ferritin with biomarkers and anthropometry were assessed with Spearman correlation (rs ) or linear regression with log10 -transformed variables, if skewed. Results: Among infants, plasma ferritin was 118 (70, 182) μg/L, Hb 111 ± 11 g/L; and AGP 0.91 (0.68, 1.17) g/L, with 40.5% of infants inflamed (AGP > 1.00 g/L). Among mothers, ferritin was 60 (38, 88) μg/L and Hb 121 ± 10 g/L. Ferritin was lower in boys (n = 200) than girls (n = 178) [102 (58, 159) vs 142 (87, 212) μg/L], but weight (5.4 ± 0.6 vs 4.9 ± 0.8 kg) and weight gain since birth (2.8 ± 0.5 vs 2.4 ± 0.7) were higher (all p < 0.0001). When adjusted for sex, infant ferritin was positively associated with AGP (p = 0.025). Adjusted for AGP and low birth weight status, each 1 kg gain in weight from birth to 3 months was associated with 32.0% lower ferritin (95%CI: −45.7, −14.9; p = 0.001) in boys, but not girls [8.4% lower ferritin (95%CI: −21.6, 7.1; p = 0.269)]. Ferritin was not associated with infant Hb (rs = 0.02), or maternal ferritin (rs = −0.003) or Hb (rs = −0.001) (all p > 0.05). Conclusions: Infant ferritin was unassociated with aspects of maternal or infant iron status. It was associated positively with AGP, which was commonly elevated, and negatively with growth in boys, whose size and rate of growth exceeded that of girls. Funding Sources: Bill and Melinda Gates Foundation.